Effect of incorporation of graphite nanoparticles on wear characteristics of Mg-WC nano-composites in dry sliding condition. (2nd January 2023) - Banerjee, S.; Sutradhar, G.; Sahoo, P.
ABSTRACT: The current work scrutinises the effect of incorporating WC and graphite (Gr) nanoparticles on the tribological characteristics of Mg-based hybrid nano-composites for different wt.% of WC and Gr. Hybrid nano-composites were synthesised using ultrasonic vibration associated with the stir casting technique. Synthesised nano-composites were characterised in detail using optical microscopy (OM), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Characterisation confirms superior microstructural integrity compared to the base alloy Mg AZ31 and also confirms particle inclusion. Microhardness values of as-cast hybrid nano-composites were also observed. The addition of 1 wt.% of Gr nanoparticles enhances the microhardness of Mg-1WC and Mg-2WC nano-composites. A pin-on-disk tribotester was used to carry out the tribological tests, using various loads (10 N–40 N) and sliding speeds (0.1 m s −1 –0.4 m s −1 ). Mg-WC nano-composites with 1 wt.% of nano-Gr show better results than those with 2 wt.% of nano-Gr. The coefficient of friction (COF) of Mg-2WC-1Gr is the lowest, followed by Mg-1WC-1Gr, Mg-1WC-2Gr and Mg-2WC-2Gr. Roughness values of worn surfaces were also examined. The worn surface of the Mg-2WC-1Gr sample shows minimum roughness. Worn surfaces were also examined under SEM to reveal wear mechanisms. Abrasion is the most dominant for hybrid nano-composites with 1 wt.% of Gr, while delamination is the most dominant for those with 2 wt.% of Gr.